Influence E-Commerce Regarding Consumer Behavior On The Shopee Application - Vita Dhameria; Nunung Nurnilasari; Mahmud Mahmud; Nana Noviada Kwartawati (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
The aim of this research is to examine the influence of e-commerce on student consumer behavior. A total of 150 respondents who had shopped at Shopee e-commerce participated in this research. This research instrument has passed validity and reliability tests through outer model measurements consisting of convergent validity, discriminant validity and composite reliability. The software used in these three stages is SEM - AMOS, this research is categorized as a cross-sectional study where data is collected only once in one time period. The sampling technique using purposive sampling is limited to certain types of people who can provide the desired information. The results of hypothesis testing concluded that e-commerce had a positive and insignificant influence on self-control. Lifestyle has a positive and significant influence on self-control. E-commerce, Lifestyle, Self control has a positive and significant influence on consumer behavior.